Strategi Pembelajaran Diferensiasi Untuk Menanamkan Kebiasaan Shalat di SDN 2 Kalahang - Hatmiah Hatmiah (STIT Syekh Muhammad Nafis Tabalong, 2024)
This research focuses on the application of the habituation method in prayer coaching at SDN 2 Kalahang. The main goal is to instill the character of discipline in students as an effort to prevent negative behavior. The habituation method was chosen to protect students from negative influences and produce a school culture based on religious values. This research is qualitative in nature with research subjects including various parties at the school and data collection techniques such as observation, interviews and documentation. The results of the research show that the policy for implementing the habituation method has been agreed upon by stakeholders in the school, and its implementation is carried out through the Dhuha prayer activity which is mandatory for all students. The application of this method is considered effective because the religious values instilled through habituation can stick with students until adulthood, forming a character based on pious deeds and noble morals. Prayer is also made into school culture with punishments for students who do not participate in prayer activities. This is done to instill character in students, with a focus on values such as 'ubudiyah', al-karimah morals, discipline and togetherness.